Literature Review: Dampak Model Pembelajaran Langsung dalam Pembelajaran Biologi - Muliana GH; Muhammad Syahrul; Zuhrah Adminira (PT. Ininnawa Paramacitra Edukasi, 2024)
This research aims to describe the literature review on the direct instruction model in Biology education, assessing its efficiency and relevance in contemporary learning settings. The research method employed is Systematic Literature Review (SLR). The data sources for this study are articles from national research journals published within the last 7 years, spanning from 2018 to 2024. The research stages in this literature review consist of 6 stages, namely research topic selection, literature search, article reduction, article display, discussion, and conclusion. The findings indicate that the direct instruction model, particularly in practical-based learning, has a positive and effective impact on students' learning outcomes and scientific process skills in the field of Biology. Keywords: Systematic Literature Review (SLR), direct instructional model, Biology